The Application of the Rebus Sic Stantibus Principle in Oil Sales and Purchase Agreements by PT Pertamina (Persero) Amidst Geopolitical Instability in the Middle East - Budi Constantin Sihombing; Roida Nababan; Samuel Situmorang (PT FORMOSA CENDEKIA GLOBAL, 2026)
Geopolitical instability in the Middle East—triggered by armed conflict, economic sanctions, disruptions to energy distribution routes, and global oil price fluctuations—has brought about significant changes in the execution of international crude oil sales contracts. These conditions potentially affect the ability of the parties involved, including PT Pertamina (Persero), to fulfill their agreed-upon contractual obligations. This study aims to analyze whether geopolitical instability in the Middle East can be classified as a